PENERAPAN METODE INKLUSI ORIENTASI BERMAIN UNTUK MENINGKATKAN MINAT KEAKTIFAN DAN HASIL BELAJAR PASSING BOLA BASKET SISWA KELAS XI-3 SMA NEGERI 2 PENAJAM PASET UTARA SEMESTER GENAP 2021/2022 - Nurnaningsih (Bajang Institute, 2022)
A basketball game with basic dribbling, passing, shooting techniques and one of the games that requires skill. The learning situation / condition for the majority of students has difficulties, this is because the learning pattern does not match the circumstances and abilities of different students, with a tendency to like to play, problem solving is needed. The purpose of this study is to increase the interest, activeness, and learning outcomes of basketball passing students of SMA Negeri 2 Penajam Paser Utara by applying inclusion or coverage methods that provide students' choices at the limit of their abilities. Research methods and techniques use class action research, the research subjects totaled 36 students of class XI.. The variables studied include methods, active interests, learning outcomes with a 2-cycle learning scenario. Each of them is designed in four stages; planning, action, observation and reflection. Data analysis uses percentage techniques, recording learning events through performance test instruments, and observations. The results showed cycle 1, the instrument of observing student activeness interest obtained an average score of 79.91 with a percentage of 74.36%, and the completion of the average results of individual student learning was 75.64, with a classical percentage of 66.67%. Because it has not yet reached the determination of the success indicator of 85%, cycle 2 is continued, and there is an increase in active interest with an average score of 85.47 with a percentage of 92.31%. for individual learning completion got 86.06, classically 89.74%. Thus through this learning process students have an interest, activeness in improving the learning outcomes of basketball passing with feelings of pleasure, joy and fun.